The juxtaposition of the posthuman and transhuman in the dystopian genre: An analysis of the Divergent and The 5th Wave trilogies - Eduardo Marks de Marques; Ânderson Martins Pereira (Ilha do Desterro, 2017)
This paper aims to discuss the way the philosophical currents of transhumanism and posthumanism re-signify the human component in contemporary dystopias. In this sense, we aim to compare the trilogies Divergent and The Fifth Wave, two narratives that are symptoms of the current Western political and social moment, but distinct in their philosophical imputations about the epistemological ideals of transhumanism and posthumanism. As such, this article is based on the works of Hayles (1999), Wolfe (2009), More e Vitta-More (2013) and Marks de Marques (2014). This work is justified to contribute with the studies about dystopia, which have stood out in recent decades and have made available new tools for dealing with the genre and the society in which it is originated.